(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
This article presents the price as the primary determinant in the selection of a supplier of logistics services. The logistics operator provides basic logistics services and additional services that increase their value. The individual customer that is found at the end of the logistics chain decides about the choice of a logistics operator. An analysis of a pricing strategy allows one to provide logistics services on a high level with the use of competitive prices and the shortest lead time possible.